Low thermal emissive surface properties of ZnO/polyimide composites prepared by pulsed laser deposition - Babrekar, Harshada A.; Jejurikar, S. M.; Jog, Jyoti Prakash; Adhi, K. P.; Bhoraskar, S. V. (Applied Surface Science, 2011)
We report the low thermal-emissive surface properties of composites of ZnO-polyimide. The composites were synthesized by depositing ZnO on polyimide surface by pulsed laser deposition technique. ZnO target was ablated at different incident energy densities and the substrate (polyimide) was held at elevated temperature. This facilitated the c-axis oriented growth of ZnO, which was inferred from the X-ray diffraction analysis. The composites consisted of multilayers having different electrical resistivities. The values of which are also estimated from Hagen-Rubens relation. The reduced infrared emissivities of the composite films, as compared to polyimide, were correlated to the increased carrier concentration and reduced surface resistivity estimated from the Hall measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: pulsed laser deposition; Thermal emissivity; Thin films; Zinc oxide

Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)